DINAMIKA POLA ASUH KELUARGA ORANG TUA BERCERAI DALAM PEMBENTUKAN KARAKTER ANAK USIA GOLDEN AGE - Annisaul A'malina; Aris Naeni Dwiyanti (STKIP Subang, 2026)
Divorce leads to changes in family structure that affect parenting patterns and children’s character development, especially during the “golden age,” which is a critical period in an individual’s development. This study aims to analyze the dynamics of parenting patterns among divorced parents and their implications for the character development of children in the “golden age.” The study employs a qualitative approach using a case study design conducted in Jangrana Village, Kesugihan Subdistrict, Cilacap Regency. Data were collected through in-depth interviews, observations, and documentation. Research findings indicate that divorce gives rise to parenting dynamics characterized by the dominance of one parent or the extended family, reduced involvement of one parent, inconsistencies in the provision of financial support and emotional support, and changes in family communication patterns. These conditions influence children’s character development to varying degrees within each family. Children who receive warm, consistent care supported by cooperation between the family and school demonstrate more positive character development, including discipline, responsibility, emotional regulation, and social skills. Conversely, inconsistent parenting tends to be associated with poor emotional regulation, low self-confidence, and limited social interaction skills. This study confirms that the quality of parenting after divorce, not the divorce itself is the primary factor in the character development of children during the “golden age.”